Higher Order Risk Preferences: Experimental Measures, Determinants and Related Field Behavior - Sebastian O. Schneider; Matthias Sutter (ZBW - Leibniz Information Centre for Economics, 2020)
Higher order risk preferences are well-known for their relation with precautionary saving or portfolio allocation. Theoretically, they are also connected with other important behavior, such as health-related or eco-friendly behavior, but these relations have never been investigated with field data. In a large-scale experiment with 658 adolescents, we relate experimental measures of higher order risk preferences with field behavior. Field behavior is collected in an extensive survey, where we focus on general risk taking, the environmental and the health domain, particularly on addictive behavior. Using a novel method allowing the experimental elicitation of intensities of prudence and temperance, we find females behaving more risk averse, prudent and temperant, and high-ability students behaving less risk averse and temperant. We confirm previous findings on financial decision making and higher order risk preferences, and find that prudence is a strong predictor for health-related behavior: An index capturing the obsessive use of smartphones is predicted significantly by prudence, but not by risk aversion or temperance.
Keywords: C93; D81; D91; J13; 330; Higher order risk; prudence; temperance; field behavior; adolescents; health; addictive behavior; smartphone addiction